2017
DOI: 10.1007/s40596-017-0800-7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychological Distress and Perception of Emotional Support in Medical Students and Residents and Implications for Educational Institutions

Abstract: Our results point to the important opportunity universities and medical schools have promoting MSR well-being by reducing institutional stressors, as well as teaching and promoting self-care and burnout avoidance techniques, instituting wellness interventions, and developing programs to identify and support at risk and distressed students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
12

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 34 publications
4
46
0
12
Order By: Relevance
“…In addition, certain personal characteristics such as being married (Robles et al, ; Brumpton et al, ; DeWitt et al, ) and difficulties in relationships (Zhang et al, ; Squires et al, ), have also been reported to heighten the sensitivity of students to stressful experiences. Moreover, research studies in the United States seem to indicate that females students, as compared to their male counterparts, appear to be more vulnerable to burnouts (Abeysekera and Dawson, ; Luthar, ; Yan et al, ; McLuckie et al, ). This has been proposed to be due to a greater propensity of females to internalize depressive feelings (Delany et al, ; Kenney et al, ) and experience increased generalized anxiety (Kessler, ; Dyrbye et al, ; Liao et al, ; Dyrbye et al, ).…”
Section: Challenges Of Present‐day Health Care Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, certain personal characteristics such as being married (Robles et al, ; Brumpton et al, ; DeWitt et al, ) and difficulties in relationships (Zhang et al, ; Squires et al, ), have also been reported to heighten the sensitivity of students to stressful experiences. Moreover, research studies in the United States seem to indicate that females students, as compared to their male counterparts, appear to be more vulnerable to burnouts (Abeysekera and Dawson, ; Luthar, ; Yan et al, ; McLuckie et al, ). This has been proposed to be due to a greater propensity of females to internalize depressive feelings (Delany et al, ; Kenney et al, ) and experience increased generalized anxiety (Kessler, ; Dyrbye et al, ; Liao et al, ; Dyrbye et al, ).…”
Section: Challenges Of Present‐day Health Care Educationmentioning
confidence: 99%
“…However, while an increasing volume of evidence has incriminated the stress associated with an excessive study load as the prime causative factor for the loss of IM, other identifiable factors also exist. In the early phases of the program, students have reported experiencing greater stress due to a perceived lack of support from educators (Dev et al, 2019), regret in choosing health care as a career (Rodriguez Zivic et al, 2013;Yan et al, 2017;Rotenstein et al, 2016), competitiveness among students (Schubert, 2016;Jackson et al, 2019), poor peer relations (West et al, 2016;McLuckie et al, 2018), and previous history of recreational drug use (Elmore et al, 2016;Yang and Shanks, 2018). The most common reasons identified by students in the later part of the program include extended work hours (Skodova and Lajciakova, 2013;Yan et al, 2017;McLuckie et al, 2018), erratic clinical rotations (Rodriguez Zivic et al, 2013;Kreitzer and Klatt, 2017), acuity of clinical cases encountered during training (Voltmer et al, 2013;Elmore et al, 2016), and even exposure to cynical colleagues (Skodova et al, 2017).…”
Section: Challenges Of Present-day Health Care Educationmentioning
confidence: 99%
See 3 more Smart Citations